2,5-Anhydro-N-benzyl-2-C-methyl-D-arabinonamide [(2S,3R,4R)-N-benzyl-3,4-dihydroxy-2-methyltetrahydrofuran-2-carboxamide] - Cox, D; Hakansson, A; Fleet, G; Watkin, D (2007)
The size of the ring and relative configuration of the chiral centres in the title compound, C13H17NO4, formed by the preferential formation of the hindered five-membered ring tetrahydrofuran rather than the expected three-membered ring epoxide, was established by X-ray crystallographic analysis; the absolute configuration was determined by the use of 2-C-methyl-D-arabinono-lactone as the starting material. The crystal structure consists of hydrogen-bonded layers lying with their hydrophobic surfaces in contact. © 2007 International Union of Crystallography All rights reserved.